2021
DOI: 10.1093/ofid/ofab466.036
|View full text |Cite
|
Sign up to set email alerts
|

36. Clinical Features of and Risk Factors for 30-day Readmission after an Initial Hospitalization with COVID-19

Abstract: Background Little is known about risk factors for readmission after COVID-19 hospitalizations. Knowledge of these factors may help to identify patients at increased risk and may help to prevent these rehospitalizations. Methods This historical cohort study was conducted at a tertiary care academic medical center. We included COVID-19 cases diagnosed by reverse-transcriptase polymerase-chain-reaction (RT-PCR) assay between Mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
2
0
0
Order By: Relevance
“…Like in this study subject to comorbidities generally predicting post-acute COVID-19 sequalae at 14 % (R 2 =0.14), another study established overall severity of comorbidities as one the strongest risk factors for post-acute COVID-19 sequelea 72 . Hospital re-admission contributing to over 17 % of post-acute COVID-19 sequalae as per this study, similar findings have shown some consistency where patients (19.9%) who survived COVID-19 hospitalization were readmitted 78 , and another, the readmission rate was 13.3% 79 .…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Like in this study subject to comorbidities generally predicting post-acute COVID-19 sequalae at 14 % (R 2 =0.14), another study established overall severity of comorbidities as one the strongest risk factors for post-acute COVID-19 sequelea 72 . Hospital re-admission contributing to over 17 % of post-acute COVID-19 sequalae as per this study, similar findings have shown some consistency where patients (19.9%) who survived COVID-19 hospitalization were readmitted 78 , and another, the readmission rate was 13.3% 79 .…”
Section: Discussionsupporting
confidence: 82%
“…Hospital re-admission contributing to over 17 % of post-acute COVID-19 sequalae as per this study, similar findings have shown some consistency where patients (19.9%) who survived COVID-19 hospitalization were readmitted 78 , and another, the readmission rate was 13.3% 79 .…”
Section: Discussionsupporting
confidence: 82%